IMPLEMENTASI PRESENSI BERBASIS SISTEM QR-CODE UNTUK MENINGKATKAN KEDISIPLINAN SISWA DAN KINERJA WAKA KESISWAAN SMK DARUT TAQWA PURWOSARI - Asrul Anan; Askhabul Kirom; Saifulah (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2021)
Pressure is one of the most important elements in teaching activities. The presence of the SMK student(s) Darut Taqwa is evidence that the attendant is present in the teaching activities, besides the presence being one of the factors of consideration and assessment in the qualification or class. The system of presence in the SMK Darut Taqwa Purwosari uses the presence of three sets, namely the presence of teachers of teachings, classrooms and fingerprints. However, in its application there are weaknesses between the manual recapitalisation of the presence so that it complicates school staff, often broken fingerprints and incompatible with the number of SMK students Darut Taqwa Purwosari cause this system to become ineffective and efficient to apply. In addition, there are still a lot of students in the Taqwa Medical School who come too late to be dismissed so as to be special attention at the time of failure to use new breakthroughs in the presence system by using the QR-Code system in order to increase student discipline. This study uses a case study approach with a qualitative method so that the data obtained are qualitative data, i.e. describing the quality of an event with a descriptive. Using the QR-Code, it facilitates the presence process due to computerization and minimizes the late arrival of students even school dropouts because the data directly recorded in the database and the presence of the students automatically informed the parents through smartphone mobile applications.